EFFECT OF CHITOSAN ON PROTEIN CONTENT IN THE MEDIUM CULTURE OF OSTEOBLASTS EXPOSED TO OXIDATIVE STRESS: EFEK KITOSAN TERHADAP KANDUNGAN PROTEIN DALAM KULTUR MEDIUM OSTEOBLAS YANG DIPAPAR DENGAN STRES OKSIDATIF - Shanty Chairani,; Sri Utami,; Dewi Fatma Suniarti, (Dentika: Dental Journal, 2011)
Chitosan is a derivative of chitin which has potential for use in bone regeneration and has been reported can stimulate bone formation. Oxidative stress as one cause of bone damage, was found increased in osteoporosis, periodontitis and arthritis. One of the species oxygen reactive (ROS), hydrogen peroxide, has been reported can inhibit osteoblast proliferation. This study was aimed to investigate the effect of various chitosan concentrations on protein content in the culture medium of human osteoblast-like cell line, MG 63, which was exposed to hydrogen peroxide. MG 63 cells were exposed to various chitosan concentrations (% w/v) 0.1, 0.2, 0.4, and 1.6%. Culture cells without chitosan were used as a control. Cells were growth with Î±-MEM medium (37ÂºC, 5% CO2) until they became confluent, then they were exposed to hydrogen peroxide for 4 hours. The protein content in the culture medium was measured by using Bradford protein assay at 655 nm wavelength. The result showed that hydrogen peroxide decreased protein concentration in the medium culture compared with group without hydrogen peroxide. Treatment group with chitosan concentration 0.4% and 1.6% exhibited a significant increasing of protein concentration in osteoblast culture medium compared with control. In conclusion, in osteoblast culture medium chitosan can inhibit the decreasing of total protein concentration which was caused by oxidative stress.